Institutional profile: University of Florida Health Personalized Medicine Program. (April 2017) - Cavallari, Larisa H; Weitzel, Kristin W; Elsey, Amanda R; Liu, Xinyue; Mosley, Scott A; Smith, Donald M; Staley, Benjamin J; Winterstein, Almut G; Mathews, Carol A; Franchi, Francesco; Rollini, Fabiana; Angiolillo, Dominick J; et al.
The University of Florida (UF) Health Personalized Medicine Program launched in 2012 with CYP2C19 genotyping for clopidogrel response at UF Health Shands Hospital. We have since expanded CYP2C19 genotyping to UF Health Jacksonville and established the infrastructure at UF Health to support clinical implementation for five additional gene–drug pairs: TPMT –thiopurines, IFNL3 ( IL28B )–PEG IFN-α-based regimens, CYP2D6 –opioids, CYP2D6/CYP2C19 –antidepressants and CYP2C19 –proton pump inhibitors. We are contributing to the evidence based on outcomes with genotype-guided therapy through pragmatic studies of our clinical implementations. In addition, we have developed a broad array of educational programs for providers, trainees and students that incorporate personal genotype evaluation to enhance participant learning.